STUDI TENTANG EFEKTIVITAS TADARUS AL-QUR`AN DALAM PEMBINAAN AKHLAK DI SMPN 8 YOGYAKARTA - Zuhri, Muhammad Noer Cholifudin (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2013)
A habit-forming activity of Tadarus in SMP N 8 Yogyakarta is an essential and integral part of other activities to build noble characters among students, such as prayers, praying together, living clean, discipline, class duty, flag ceremonies and charity work. Having regular activity of Tadarus in public school attracts many attentions to study it in greater depth. By employing naturalistic qualitative approach, this research was aimed to reveal the background and implementation of Tadarus and its effectiveness as a mean of studentsâ morals building.The results showed that, firstly Tadarus was held regularly every morning about 15 minutes before the first period. The school principal was in charge of the activity, while the religion teacher functioned as a coordinator to run the program helped by all teachers of SMP N 8 Yogyakarta. Secondly, Tadarus al - Qur`an was proven effective to build studentsâ morals. The effectiveness could be seen from several aspects, such as: 1) aspect of the duty and function, in which the teacher had taken the roles as a supervisor and guide on the process of activities, in other hand, students showed responsibility to carry out the activities seriously, 2) planning/ program, Tadarus became an integral part of school activities that had been well-prepared and organized systematically, 3) provisions/rules, it had been conducted by using well-organized techniques, and 4) aspect of goals, the ultimate objective of Tadarus had been achieved that was equipping students with a commendable character and far from despicable character.Â ÙØ§Ù ØªØ¹ÙÙØ¯ ÙØ´Ø§Ø· "ØªØ¯Ø§Ø±Ø³ Ø§ÙÙØ±Ø¢Ù" ÙÙ Ø§ÙÙØ¯Ø±Ø³Ø© Ø§ÙÙØªÙØ³Ø·Ø© Ø§ÙØ¹Ø§ÙØ© Ø§ÙØÙÙÙÙØ© Ø¬ÙÙØ¬Ø§ÙØ±ØªØ§ Ø¹ÙØµØ±Ø§ ÙÙÙØ§ ÙØªÙÙÙÙ Ø§ÙØ£Ø®ÙØ§Ù Ø§ÙÙØ±ÙÙØ© Ø¨Ø¬Ø§ÙØ¨ Ø§ÙØ£ÙØ´Ø·Ø© Ø§ÙØ£Ø®Ø±Ù ÙØ«Ù ØµÙØ§Ø© Ø§ÙØ¬ÙØ§Ø¹Ø©Ø ÙØ§ÙØ°ÙØ± Ø¬ÙØ§Ø¹ÙØ§Ø ÙØ§ÙÙØØ§ÙØ¸Ø© Ø¹ÙÙ Ø§ÙÙØ¸Ø§ÙØ©Ø ÙØ§ÙØ§ÙØ¶Ø¨Ø§Ø·Ø ÙØªÙØ³ÙÙ Ø§ÙÙØ¸ÙÙØ© ÙÙ Ø§ÙÙØµÙØ ÙÙØ´Ø§Ø· Ø§ÙÙØ±Ø§Ø³ÙØ ÙØ§ÙØ¥ÙÙØ§Ù. ÙØ£ØµØ¨Ø ÙØ´Ø§Ø· "ØªØ¯Ø§Ø±Ø³ Ø§ÙÙØ±Ø¢Ù" Ø¬Ø°Ø§Ø¨Ø§ ÙÙØ¯Ø±Ø§Ø³Ø© ÙØ§ÙØ¨ØØ« ÙÙÙ. ØØ§ÙÙ ÙØ°Ø§ Ø§ÙØ¨ØØ« â Ø¨Ø§ÙÙØ¯Ø®Ù Ø§ÙÙÙÙÙ Ø§ÙØ·Ø¨ÙØ¹Ù â ÙÙÙØ´Ù Ø¹Ù Ø§ÙØ®ÙÙÙØ© ÙØªØ·Ø¨ÙÙ ÙØ´Ø§Ø· "ØªØ¯Ø§Ø±Ø³ Ø§ÙÙØ±Ø¢Ù â ÙÙØ¹ÙØ§ÙÙØªÙ ÙÙØ³ÙÙØ© ÙØªÙÙÙÙ Ø§ÙØ£Ø®ÙØ§Ù Ø§ÙÙØ±ÙÙØ©. ÙØªØ§Ø¦Ø¬ ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ : Ø£ÙÙØ§Ø Ø¹ÙØ¯ ÙØ°Ø§ Ø§ÙÙØ´Ø§Ø· ÙÙØ¯Ø© Ø±Ø¨Ø¹ Ø³Ø§Ø¹Ø© ÙØ¨Ù Ø§ÙØØµØ© Ø§ÙØ£ÙÙÙØ ÙØ§ÙÙØ³Ø¤ÙÙ ÙÙ Ø±Ø¦ÙØ³ Ø§ÙÙØ¯Ø±Ø³Ø© ÙÙØ¯Ø±Ø³ Ø§ÙØ¯ÙÙ Ø§ÙØ¥Ø³ÙØ§ÙÙ ÙØ§ÙÙÙØ¸Ù ÙØ§ÙÙØ¯ÙØ± ÙØ§ÙÙØ§Ø¦Ù Ø¨Ù Ø¬ÙÙØ¹ ÙØ¯Ø±Ø³ Ø§ÙÙØ¯Ø±Ø³Ø© Ø§ÙÙØªÙØ³Ø·Ø© Ø§ÙØ¹Ø§ÙØ© Ø§ÙØÙÙÙÙØ© 8 Ø¬ÙÙØ¬Ø§ÙØ±ØªØ§. Ø«Ø§ÙÙØ§Ø ÙØ§Ù ÙØ°Ø§ Ø§ÙÙØ´Ø§Ø· ÙØ¹ÙØ§ÙØ§ ÙÙ ØªÙÙÙÙ Ø£Ø®ÙØ§Ù Ø§ÙØ·ÙØ§Ø¨. ÙÙØ°Ù Ø§ÙÙØ¹Ø§ÙÙØ© ØªØ¸ÙØ± ÙÙ Ø§ÙØ¬ÙØ§ÙØ¨ Ø§ÙØªØ§ÙÙØ© : 1) Ø§ÙÙØ¸ÙÙØ© ÙØ§ÙØ¯ÙØ±. ÙØ§Ù Ø§ÙÙØ¯Ø±Ø³ÙÙ Ø¨Ø¯ÙØ± Ø§ÙØªÙØªÙØ´Ø ÙØ§ÙÙØ±Ø§ÙÙØ©Ø ÙØ£Ø¯Ù Ø§ÙØ·ÙØ§Ø¨ ÙØ°Ø§ Ø§ÙÙØ´Ø§Ø· Ø¨Ø§ÙØªÙØ§Ù ÙÙØ¹Ù. 2) Ø§ÙØ®Ø·Ø© Ø£Ù Ø§ÙÙØ´Ø§Ø·. Ø£ØµØ¨Ø ÙØ°Ø§ Ø§ÙÙØ´Ø§Ø· ÙØ´Ø§Ø·Ø§ ÙØ¯Ø±Ø³ÙØ§ Ø±ÙØªÙÙÙØ§ ÙØ¨Ø±ÙØ¬Ø§. 3) Ø§ÙÙØ¸Ø§Ù. Ø¹ÙØ¯ ÙØ°Ø§ Ø§ÙÙØ´Ø§Ø· Ø¨Ø£Ø³ÙÙØ¨ ÙØªÙÙÙØ° ÙØ¨Ø±ÙØ¬ ÙØ§Ø¶ØØ 4) Ø§ÙÙØ¯ÙØ ÙØ§ÙÙØ¯Ù ÙÙ ÙØ°Ø§ Ø§ÙÙØ´Ø§Ø· ØºØ±Ø³ Ø§ÙØ£Ø®ÙØ§Ù Ø§ÙÙØ±ÙÙØ© ÙÙ ÙÙÙØ³ Ø§ÙØ·ÙØ§Ø¨ ÙØ¥Ø¨Ø¹Ø§Ø¯ÙÙ Ø¹Ù Ø¶Ø¯ÙØ§.